Kompetensi Lulusan Prodi Humas UNJ (Studi Kasus : Kompetensi Lulusan Prodi Humas UNJ di Perusahaan Swasta DKI Jakarta) - VERA WIJAYANTI SUTJIPTO (Communicology: Jurnal Ilmu Komunikasi, 2014)
Abstract PR UNJ D3 program, established in 2004, has graduated a lot of students, but in fact many of the graduates are not working in the world of public relations, so researchers wanted to know whether the competence of graduates Prodi D3 UNJ PR practitioners to the expectations of the world? .Teori Research is the role of public relations theories contained in his book, Scott M, Cutlip, Allen H, Center and Glen M.Broom in his book Effective Public Relations is communications technician (Entry Level Technician), Expert prescriber (Project Supervisor), Communication Facilitator (Constituency Manager and issue Trend Analysis) and facilitator Troubleshooter (Director Constituency and issue Trend Analysis). Research using femenologi paradigm, where data were collected by observation and interview, then analyzed using Interpretative Phenomenological Analysis of Jonathan A. Smith. Emergent themes 4) Searching SAT for connections across emergent themes 5) Moving the next cases 6) Looking for patterns across. Key words: Humas Role, hard skills, soft skills Program D3 Humas UNJ yang berdiri pada tahun 2004, sudah meluluskan banyak sekali mahasiswa, namun ternyata banyak dari lulusan tidak bekerja di dunia humas, , sehingga peneliti ingin mengetahui apakah kompetensi lulusan Prodi D3 Humas UNJ sesuai dengan harapan dunia praktisi? .Teori penelitian yang digunakan adalah teori peran humas yang terdapat dalam bukunya Scoot M,Cutlip, Allen H, Center dan Glen M.Broom dalam bukunya Effective Public Relations yaitu teknisi komunikasi (Entry Level Technician), Expert Prescriber (Supervisor Project), Fasilitator Komunikasi (Manager Constituency and Issue Trend Analysis) dan Fasilitator Pemecah Masalah (Director Constituency and Issue Trend Analysis). Penelitian menggunakan paradigma femenologi, dimana data-data penelitian dikumpulkan dengan cara observasi dan interview, kemudian dianalisis menggunakan Interpretative Phenomenological Analysis dari Jonathan A. Smith. Emergent themes 4) Searching for connections across emergent themes 5) Moving the next cases 6) Looking for patterns across. Kata Kunci : Peran Humas, hard skills, soft skills